NDP52 interacts with mitochondrial RNA poly(A) polymerase to promote mitophagy. (11th October 2018) - Furuya, Norihiko; Kakuta, Soichiro; Sumiyoshi, Katsuhiko; Ando, Maya; Nonaka, Risa; Suzuki, Ayami; Kazuno, Saiko; Saiki, Shinji; Hattori, Nobutaka
Abstract: Parkin‐mediated mitophagy is a quality control pathway that selectively removes damaged mitochondria via the autophagic machinery. Autophagic receptors, which interact with ubiquitin and Atg8 family proteins, contribute to the recognition of damaged mitochondria by autophagosomes. NDP52, an autophagy receptor, is required for autophagic engulfment of damaged mitochondria during mitochondrial uncoupler treatment. The N‐terminal SKICH domain and C‐terminal zinc finger motif of NDP52 are both required for its function in mitophagy. While the zinc finger motif contributes to poly‐ubiquitin binding, the function of the SKICH domain remains unclear. Here, we show that NDP52 interacts with mitochondrial RNA poly(A) polymerase (MTPAP) via the SKICH domain. During mitophagy, NDP52 invades depolarized mitochondria and interacts with MTPAP dependent on the proteasome but independent of ubiquitin binding. Loss of MTPAP reduces NDP52‐mediated mitophagy, and the NDP52–MTPAP complex attracts more LC3 than NDP52 alone. These results indicate that NDP52 and MTPAP form an autophagy receptor complex, which enhances autophagic elimination of damaged mitochondria. Synopsis: The autophagy receptor NDP52 interacts with mitochondrial RNA poly(A) polymerase (MTPAP), and the NDP52‐MTPAP complex contributes to the ubiquitin‐independent recognition of damaged mitochondria by autophagy. NDP52 irrupts into mitochondria proteasome‐dependently, and interacts with MTPAP via its N‐terminal SKICH domain upon mitophagy‐inducing conditions. The NDP52‐MTPAP complex attracts more LC3 to the damaged mitochondria than NDP52 alone. NDP52 interacts with MTPAP and irrupts into mitochondria ubiquitin‐binding‐independently. Abstract : The autophagy receptor NDP52 interacts with mitochondrial RNA poly(A) polymerase (MTPAP) to promote the ubiquitin‐independent removal of damaged mitochondria by autophagy.